MEDIA PRACTICE OF PROMOTING OF THE UKRAINIAN LANGUAGE IN THE FORMAT OF LIFE HACKS - Bondarenko, Tetiana (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. In the context of Russia’s war against Ukraine and the strengthening of nationalpatriotic processes in the state, the priority task is the popularization of the Ukrainian language. It is studied by the majority of the population as the language of the titular nation. This article examines the modern media experience of popularizing the Ukrainian language in the format of life hacks and describes the author's practice of promoting language knowledge through useful tips within the cross platform resource “Mova_vtrendi”. Purpose. The study aims to investigate the media practice of popularizing the Ukrainian language in the format of life hacks and to prove the effectiveness of such resources for implementing the state language popularization strategy. Methods. The research and systematic presentation were made possible through the application of several scientific methods: theoretical method, analysis method, typology method, descriptive method, empirical method, and generalization method. Results. The essence of the basic concepts (popularization, life hack, video tutorials, YouTube Shorts, gamified content, etc.) has been clarified. The author’s vision regarding the typology of language-related life hacks is proposed, with text-image life hacks, video lessons, short videos (YouTube Shorts), podcasts, and gamified content (surveys, tests) being singled out. Originality. Media projects for the popularization of the Ukrainian language were analyzed. It is an innovative form of content that combines learning and entertainment in a convenient and compact form. Features of the author’s project «Mova_vtrendi» are described. This project aims to offer the audience language lifehacks in various formats, which make it possible to learn the language in an easy and interesting way. Conclusion. It is summarized that the strategy of popularizing the Ukrainian language involves the fluent command of the native language by Ukrainians. The use of the Ukrainian language in all spheres of public life, and the formation of a complete Ukrainian-speaking informational and cultural space. Currently, there is a high demand for educational projects aimed at popularizing the Ukrainian language. The “Mova_vtrendi” project can become an innovative resource for those who want to learn the Ukrainian language in a convenient and interactive format.